Control and eradication programme of Enzootic Bovine Leucosis (EBL) from selected dairy herds in Turkey - Burgu, I; Alkan, F; Karaoglu, T; Bilge-Dagalp, S; Can-Sahna, K; Güngör, B; Demir, B (M H Schaper Gmbh Co Kg, 2005)
Serum samples of 15 909 cattle from 31 dairy herds located in various regions of Turkey were tested for the presence of antibodies against bovine leucosis virus (BLV) using Agar Gel Immuno-diffusion technique (AGID). 48.3% (15/31) of the herds had seropositive animals and positivity rates were detected from 0.5-34.4% in these herds. In an EBL control/eradication programme all seropositive animals were culled in the infected herds. Thereafter, a total of 74 347 sera were tested for the presence of BLV specific antibodies. The serological results and detail of EBL control/eradication programme were shown in this paper.
Keywords: EBL; eradication; Turkey